PEMBERDAYAAN MASYARAKAT DALAM PROMOSI FEMINIME HYGIENE (Daun Binahong, Sirih Hijau dan Daun Mint) GUNA MENINGKATKAN PROSES PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI DESA KAPONGAN KECAMATAN KAPONGAN KABUPATEN SITUBONDO - Lea Ingne Reffita; Khoiriati Rohma; Lutfiatur Rohmani; Minnatul Innayati; Nikmatul Maula Rizka (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
The puerperal period is at risk of experiencing puerperal complications, especially in the first 3 days after delivery. One of the risks during the puerperium is infection during the puerperium which is one of the causes of maternal death. Infection can occur in the genital organs with the source of infection being a wound from the placenta, lacerations in the genital tract, including episiotomies on the perineum, vaginal wall and cervix. Perineal wounds have several factors, including maternal factors, namely parity and the process of pushing, fetal factors including baby's weight and fetal position abnormalities and delivery factors which include assisting factors, precipitous parturition, and vaginal delivery (vacuum extraction, forceps extraction, embryotomy and episiotomy). This service will be held in Kapongan Village, Kapongan District, Situbondo Regency. This community service program was conducted for 25 partners with the aim of providing information on how to process traditional medicines. After this service is carried out, it is hoped that the community will know and apply proper processing methods for the traditional medicines they usually use